MADRASAH SATU ATAP: SEBUAH ALTERNATIF? - Nurhattati Fuad (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
AbstractEvery Indonesian citizen has a right get education service. There are some the governmental policies for the sake of realizing the citizen’s right for educational service. One of such policies, is the implementation of program dealing with the educational accessibility for all of Indonesian citizen. For this purpose, on behalf of realizing the education democracy, social justice, and other basic human values and also postering the competitive capability in the global market, the Indonesian government established one roof school system what we called as the Madrasah Satu Atap (MSA). In principle, this Islamic school system is based on the one system of management in carrying out the two educational unit (Primary Madrasah/MI and Secondary Madrasah/MTs). This article tries to elaborate what and how the MSA an alternative model school system being developed has a significant contribution in realizing the national education policy in Indonesia.